(untitled) (Research, Society and Development, 2020)
Studies on the competitiveness of weed crops allow us to develop strategies for their management, since they can define the characteristics that give a greater competitive ability to the crops. Thus, the objective of this work was to determine the effects of the competition of brachiaria and blackthorn species and the combination of the two in different densities in maize growth. For this, an experiment was set up in a protected environment in a randomized block design using the factorial scheme 3 x 5, that is, factor A represented the community 1) corn + Bidens pilosa (black sting); Community 2) corn + Urochloa brizantha (brachiaria) and community 3) corn + Bidens pilosa + Urochloa brizantha (brachiaria). The factor B represented by 5 densities of these species. Maize plants are negatively affected by competition with weeds in the different combinations evaluated, and the most damaging combination for maize was the one in which the crop developed with increasing black-spot densities. The combination where the corn competed with the two weeds at proportional densities affected corn growth less than the treatment where the crop grew with dicotyledon.